From Kinship to Collegiality: Changing Literati Networks, 1100-1400 - Bol, Peter K. (Journal of Historical Network Research, 2021)
<span class="docData;DOCY;v5;3150;BQiAAgAAEYQCAAAGiAIAAANPCQAABV0JAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAAwwYAAAC+BgAAAWsAAAAVBggAAAAxADIAMAA5AAEGAAAAAAkGCQAAACcEFAEAAAsBARoGPAAAAAQGEAAAAFAAYQBsAGEAdABpAG4AbwAFBhAAAABQAGEAbABhAHQAaQBuAG8ABgYKAAAASwBhAGkAVABpABsGAAAAAAJJBgAABRMBAAABPAAAAAQGEAAAAFAAYQBsAGEAdABpAG4AbwAFBhAAAABQAGEAbABhAHQAaQBuAG8ABgYKAAAASwBhAGkAVABpAAjNAAAAAMgAAABUAGgAaQBzACAAaQBzACAAcwB0AHUAZAB5ACAAbwBmACAAYwBoAGEAbgBnAGUAcwAgAGkAbgAgAGsAaQBuAHMAaABpAHAAIABhAG4AZAAgAHMAYwBoAG8AbABhAHIAbAB5ACAAYQBzAHMAbwBjAGkAYQB0AGkAbwBuACAAaQBuACAAVwB1AHoAaABvAHUALAAgAGEAIABwAHIAZQBmAGUAYwB0AHUAcgBlACAAaQBuACAAdABoAGUAIABtAGkAZABkAGwAZQAgAAVLAgAAATwAAAAEBhAAAABQAGEAbABhAHQAaQBuAG8ABQYQAAAAUABhAGwAYQB0AGkAbgBvAAYGCgAAAEsAYQBpAFQAaQAIBQIAAAAAAgAAbwBmACAAWgBoAGUAagBpAGEAbgBnACAAcAByAG8AdgBpAG4AYwBlAC4AIABUAGgAZQAgAGcAZQBvAGcAcgBhAHAAaABpAGMAIABlAHgAdABlAG4AdAAgAG8AZgAgAGwAaQB0AGUAcgBhAHQAaQAgAGsAaQBuAHMAaABpAHAAIABjAG8AbgBuAGUAYwB0AGkAbwBuAHMAIABiAGUAYwBhAG0AZQAgAGkAbgBjAHIAZQBhAHMAaQBuAGcAbAB5ACAAbABvAGMAYQBsACAAZgByAG8AbQAgAHQAaABlACAAdAB3AGUAbABmAHQAaAAgAGMAZQBuAHQAdQByAHkAIABvAG4ALAAgAGIAdQB0ACAAcABhAHIAYQBkAG8AeABpAGMAYQBsAGwAeQAgAHQAaABlACAAawBpAG4AcwBoAGkAcAAgAGMAbwBuAG4AZQBjAHQAaQBvAG4AcwAgAGEAYwByAG8AcwBzACAAdABoAGUAIABwAHIAZQBmAGUAYwB0AHUAcgBlACAAZABlAGMAbABpAG4AZQBkACAAYQBzACAAdwBlAGwAbAAuACAASABvAHcAZQB2AGUAcgAsACAAYQB0ACAAdABoAGUAIABzAGEAbQBlACAAdABpAG0AZQAgAGMAcgBvAHMAcwAtAHAAcgBlAGYAZQBjAHQAdQByAGUAIAAFXQAAAAE8AAAABAYQAAAAUABhAGwAYQB0AGkAbgBvAAUGEAAAAFAAYQBsAGEAdABpAG4AbwAGBgoAAABLAGEAaQBUAGkACBcAAAAAEgAAAHMAYwBoAG8AbABhAHIAbAB5AAWVAAAAATwAAAAEBhAAAABQAGEAbABhAHQAaQBuAG8ABQYQAAAAUABhAGwAYQB0AGkAbgBvAAYGCgAAAEsAYQBpAFQAaQAITwAAAABKAAAAIABjAG8AbgBuAGUAYwB0AGkAbwBuAHMAIABhAG0AbwBuAGcAIABsAGkAdABlAHIAYQB0AGkAIABpAG4AYwByAGUAYQBzAGUAZAAFYQAAAAE8AAAABAYQAAAAUABhAGwAYQB0AGkAbgBvAAUGEAAAAFAAYQBsAGEAdABpAG4AbwAGBgoAAABLAGEAaQBUAGkACBsAAAAAFgAAACwAIABiAGUAYwBvAG0AaQBuAGcAIAAFeQAAAAE8AAAABAYQAAAAUABhAGwAYQB0AGkAbgBvAAUGEAAAAFAAYQBsAGEAdABpAG4AbwAGBgoAAABLAGEAaQBUAGkACDMAAAAALgAAAHQAaABlACAAbgBlAHcAIABmAG8AdQBuAGQAYQB0AGkAbwBuACAAZgBvAHIAIAAFXQAAAAE8AAAABAYQAAAAUABhAGwAYQB0AGkAbgBvAAUGEAAAAFAAYQBsAGEAdABpAG4AbwAGBgoAAABLAGEAaQBUAGkACBcAAAAAEgAAAGwAaQB0AGUAcgBhAHQAaQAgAAVtAAAAATwAAAAEBhAAAABQAGEAbABhAHQAaQBuAG8ABQYQAAAAUABhAGwAYQB0AGkAbgBvAAYGCgAAAEsAYQBpAFQAaQAIJwAAAAAiAAAAZwByAG8AdQBwACAAcwBvAGwAaQBkAGEAcgBpAHQAeQAuAAUKAAAAAQAAAAAIAAAAAAUKAAAAAQAAAAAIAAAAAAUKAAAACAUAAAANAAAAAAoAAAAAAAAAABEAAAAA7QIAAAAtAAAAAQYAAAAACQYbAAAAJwQUAQAACwEBHAEAKAQAAAAAHQEAKQTIAAAAGwYAAAAAAYwAAAAEBg4AAABDAGEAbABpAGIAcgBpAAUGDgAAAEMAYQBsAGkAYgByAGkABwYOAAAAQwBhAGwAaQBiAHIAaQAGBg4AAABDAGEAbABpAGIAcgBpAAgEFgAAABYEFgAAABkGCgAAAGQAZQAtAEQARQAaBgoAAABhAHIALQBTAEEAGwYKAAAAZQBuAC0AVQBTAAIlAgAAACACAAABCAAAADEAMgAwADkAAhoAAABKAEgATgBSACAAQQBiAHMAdAByAGEAYwB0AAkBAAAAAwMIAAAAMQAxADgAMwASCAAAADEAMgAxADAACgEAAAABBd8AAAAAAQABAQACAQADAQAEBhQAAABDAG8AbgBzAHQAYQBuAHQAaQBhAAUGFAAAAEMAbwBuAHMAdABhAG4AdABpAGEABwYOAAAAQwBhAGwAaQBiAHIAaQAGBg4AAABDAGEAbABpAGIAcgBpAAgEFgAAAAkDWVlZCgEADAEAJgQAAAAADwEAEAEAEQEAJwQAAAAAFAEAFQEAFgQWAAAAFwEAGAEAGQYKAAAAZQBuAC0AVQBTABoGCgAAAGEAcgAtAFMAQQAbBgoAAABlAG4ALQBVAFMAHAYGAAAAAQEPAgGmHgEABt8AAAAAAQABBhIAAAAkBAAAAAAlBAAAAAAmBAAAAAAFAQEGAQAHAQAIAQAJBhsAAAAnBAQBAAALAQIcAQAoBAAAAAAdAQApBMgAAAAOBggAAAAAAQEBA////xkBARsGfQAAAAAUAAAAAAMAAAAFBAAAAAAGBAQAAAADAQABFAAAAAADAAAABQQAAAAABgQEAAAAAwEAAhQAAAAAAwAAAAUEAAAAAAYEBAAAAAMBAAMUAAAAAAMAAAAFBAAAAAAGBAQAAAADAQALFAAAAAADAAAABQQAAAAABgQEAAAAAwEALAEAEwEAAAAB">This is a study of changes in kinship and scholarly association in Wuzhou, a prefecture in the middle of Zhejiang province. The geographic extent of literati kinship connections became increasingly local from the twelfth century on, but paradoxically the kinship connections across the prefecture declined as well. However, at the same time, cross-prefecture scholarly connections among literati increased, becoming the new foundation for literati group solidarity.